Altruism in the living space of Russian youth - Antonova, Natalya; Lopatina, Viktoria; Šljukić, Srđan (Sociološki pregled, 2026)
The goal of our study was to identify how altruism is understood and implemented in the living space of young people. The methodological basis of the study was an online survey (n = 641) and a series of semi-structured interviews (n = 10) with young people from Yekaterinburg and the Sverdlovsk region aged 18 to 30. The results of the study showed that most young people define altruism as selfless help associated with empathy, responsibility and the desire to make the world a better place. The most common forms of altruism are everyday actions. At the same time, wariness is recorded regarding helping strangers. The conclusion emphasizes that altruism retains a stable value among Russian youth and is an important element of social integration and civic activity.